ANALISIS KEGIATAN GREEN SCHOOL TERHADAP KARAKTER PEDULI LINGKUNGAN DI TK ABA IV KOTA JAMBI - Tasqiyah Juliamezain; Evita Anggereini; Akhmad Fikri Rosyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of instilling an environmentally conscious character from an early age (the “golden age”) to foster positive habits in preserving the surrounding ecosystem. One concrete effort that educational institutions can undertake is through the Green School program. This study aims to describe and analyze the implementation of Green School activities in shaping an environmentally conscious character among early childhood students at TK ABA IV in Jambi City. This is a quantitative descriptive study. The population in this study comprises all students in Group B at TK ABA IV in Jambi City, totaling 32 children (16 children in Class B1 and 16 children in Class B2). Using total sampling, the entire population was selected as the study sample, consisting of 32 children. Data collection was conducted through observation, questionnaires completed by teachers, and documentation of activities. Data analysis was performed using descriptive statistical percentages to provide a real and factual quantitative picture of the variables under study. The research findings indicate that the implementation of the Green School program at TK ABA IV in Jambi City has been effectively integrated into the environmentally conscious curriculum through the use of materials made from natural or recycled resources and the creation of a school garden. Overall, the Green School activities have been effective and have had a significant positive impact on fostering children’s environmental awareness. The children have demonstrated positive behavioral changes, such as disposing of trash in the proper bins independently, helping to maintain classroom cleanliness, and actively participating in caring for and watering the school’s plants. Based on these results, it is concluded that the Green School program is effective in instilling environmental awareness values in early childhood in an educational and participatory manner. The school administration and teachers are advised to maintain and strengthen collaboration to optimize aspects of environmental habit formation that still require consistent and sustained effort.